POLSKA TRANSFORMACJA GOSPODARCZA NA TLE WYBRANYCH KRAJÓW EUROPY ŚRODKOWEJ - Kowalski, Tadeusz (Wydział Prawa i Administracji UAM, 2009)
The aim of this paper is to provide an empirical analysis of Poland’s economic transformation process. Poland’s case (its initial conditions, growth and development) is compared with the transformations that have taken place in the Czech Republic, Hungary, the Slovak Republic, Lithuania and Ukraine. The transformation process ran in two phases: a phase of stabilisation and implementation of the fundamental constitutional changes, and a phase of development. The paper offers a general overview of those phases, with a special focus on the macroeconomic context, institutional framework and development factors. It also highlights the issue of the conditions and factors of national economy competitiveness. The applied approaches complement one another, creating a context for international comparison of the operation of factors that stimulate and inhibit the transition process. While highly evaluating Poland’s economic transformation, the analysis identifies many opportunities that had not been taken. The most important ones include: lack of effective response (regarding quantitative and qualitative economic policy) to the lowest in Europe employment rate; failure to bring the privatisation process to a conclusion; reform fatigue and slowdown, also with respect to fiscal reforms which otherwise could facilitate meeting by the Polish economy o f euro area membership requirements and allow Poland to improve its competitive position. In the future, Poland’s ability to overcome the above-mentioned weaknesses will be of crucial importance. Moreover, it is essential for Poland to increase the rates of domestic savings, supply and investment. Fast changes in the GDP structure and starting effectiveness reserves that underlie the improvement of broadly understood institutional environment are also necessary.
ECONOMIC TRANSFORMATION IN POLAND AND TRANSFORMATIONS IN SELECTED CENTRAL EUROPEAN COUNTRIES